Hydrogen Effect on the Defect Structure Formation in the Zr – 1 WT.% Nb Alloy Under Pulsed Electron Beam Irradiation; Russian Physics Journal; Vol. 62, iss. 5 - Mishin I. P. Ivan Petrovich; Grabovskaya G. P. Galina Petrovna; Stepanova E. N. Ekaterina Nikolaevna; Laptev R. S. Roman Sergeevich; Teresov A. D. Anton Dmitrievich (2019, 2019)
Title screen